WEBSITE DESIGN COMMUNITY MARCHING BAND "BULLDOZER" DEPARTMENT OF PUBLIC WORK WITH PHP, MACROMEDIA DREAMWEAVER 8.0, AND MYSQL - Reddy Sufriyanto; Aqwam Rosadi Kardian, SKom, MM Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2008)
Marching Band is a sentence that may be alien in the eyes of some of the students.See how this develops, Marching Band is less enthused by some of the students,because it was considered less interesting, boring, and a waste of time. For that theauthor intends to introduce Marching Band through a Web site where students whoare surfers can search for, obtain various types of information related to the MarchingBand "Bulldozer", and can join a community marching band "Bulldozer" can furtherknow about marching band, and can interact between members of the marching band.The author also intends to prevent the students from the negative actions that areoutside school hours, by following the positive activities, one of them by followingthe activities of the marching band.